Rock Mass behavior and Cap Rock Stability at the Malmberget Mine - Umar, Sraj Banda (Luleå tekniska universitet, Geoteknologi, 2014)
Rock Mass behavior and Cap Rock Stability at the Malmberget MineThe LKAB Malmberget mine is mined using sublevel caving. This mining method requires continuous caving of the hangingwall, which also result in ground deformations on the surface. The Malmberget mine is located in the municipality of Malmberget; thus well planned residential relocations have been required as the caving area has expanded and associated ground deformations developed. This thesis aims to bring an increased understanding of the stress redistribution and likely failure mechanisms in the hangingwall of the Printzsköld orebody, one of the orebodies currently in production in Malmberget. Rock mass investigations have been conducted in the Printzsköld and Fabian orebodies to gain more understanding of the rock mass. These investigations included core logging, strength testing, borehole photography, joint mapping underground, and rock mass characterization in the Printzsköld orebody. The investigations showed that rock mass rating (RMR) scatter for Printzsköld and Fabian orebodies were 55 – 78 and 40 – 76 respectively, indicating a fair to good rock mass, albeit with some scatter and weak units present. The work also showed that there were three main joint sets in both the Printzsköld and Fabian orebodies. Conceptual continuum and discontinuum numerical analysis was conducted for the Printzsköld orebody, in order to study potential failure behavior of the hangingwall and cap rock, as well as to study the possible effects of large-scale structures inferred near the Printzsköld orebody. The results from the continuum analyses indicated high stress build-ups in the crown pillar and stress relaxation in the hangingwall of the orebody. Both shear and tensile failure were noted in the hangingwall and the cap rock. As mining proceeded to the level of 1225 meters, the stresses in the cap rock increased and the relaxation zone also increased. The hangingwall of the Printzsköld orebody can be considered as a beam fixed at the crown pillar and the cave ...